Surface disorder in c-Si induced by swift heavy ions - Bogle, Kashinath A.; Gokhale, Suresh P.; Bhoraskar, Vasant N. (Radiation Effects and Defects in Solids, 2005)
The disorders induced in crystalline silicon (c-Si) through the process of electronic energy loss in the swift heavy ion irradiation were investigated. A number of silicon <100> samples were irradiated with 65 MeV oxygen ions at different fluences, 1x10(13) to 1.5x10(14) ions/cm(2), and characterized by the Raman spectroscopy, the optical reflectivity, the X-ray reflectivity, the atomic force microscopy (AFM) and the X-ray diffraction (XRD) techniques. The intensity, redshift, phonon coherence length and asymmetric broadening associated with the Raman peaks reveal that stressed and disordered lattice zones are produced in the surface region of the irradiated silicon. The average crystallite size, obtained by analyzing Raman spectrum with the phonon confinement model, was very large in the virgin silicon but decreased to <100 nm dimension in the ion irradiated silicon. The results of the X-ray reflectivity, AFM and optical reflectivity of 200-700 nm radiation indicate that the roughness of the silicon surface has enhanced substantially after ion irradiation. The diffusion of oxygen in silicon surface during ion irradiation is evident from the oscillation in the X-ray reflectivity spectrum and the sharp decrease in the reflectivity of 200-400 nm radiation. The rise in temperature, estimated from the heat spike model, was high enough to melt the local silicon surface. The results of XRD indicate that lattice defects have been induced and a new plane <211> has been formed in the silicon <100> after ion irradiation. The results of the present study show that the energy deposited in crystalline silicon through the process of electronic energy loss similar to 0.944 keV/nm per ion is sufficient to induce disorders of appreciable magnitude in the silicon surface even at a fluence of similar to 10(13) ions/cm(2).
Keywords: AFM; crystalline silicon; ion irradiation; optical and X-ray reflectivity; Raman; XRD

Co : CdS diluted magnetic semiconductor nanoparticles: radiation synthesis, dopant-defect complex formation, and unexpected magnetism - Bogle, Kashinath A.; Ghosh, Saurabh; Dhole, Sanjay D.; Bhoraskar, Vasant N.; Fu, Lian-feng; Chi, Miao-Fang; Browning, Nigel D.; Kundaliya, Darshan; Das, Gour P.; Ogale, Satishchandra B. (Chemistry of Materials, 2008)
Incorporating a dopant into a nanoparticle is a nontrivial proposition in view of the size dependent surface versus bulk energy considerations and the intrinsic proximity of the surface to the interior, which facilitates migration to the surface. If realized and controlled, however, it can open up new avenues to novel nanomaterials. Some previous studies have shown the dopability of nanosystems but only with specific surface functionalization. Here, we demonstrate the successful dopant incorporation via a new route of pulsed high energy electron induced synthesis. We choose a system Co:CdS (dilutely cobalt doped cadmium sulfide) in view of the well-known application-worthy properties of CdS and the potential possibility of its conversion to a diluted magnetic semiconductor of interest to spintronics. By using various techniques, we show that matrix incorporation and uniform distribution of cobalt are realized in US nanocrystals without the need for additional chemical or physical manipulation. Optical and photoluminescence properties also support dopant incorporation. Interestingly, although magnetism is realized, it is weak, and it decreases at higher cobalt concentration. First principle density functional calculations are performed to understand this counterintuitive behavior. These calculations suggest that the introduction of parent cation or anion vacancies lead to magnetic moment reduction, albeit marginally. However, with some Co impurity fraction in the octahedral interstitial site inside the wurtzite cage, the magnetic moment drops down drastically. This study reveals that defect states may have an interesting role in dopant stabilization in nanosystems, with interesting system dependent consequences for the properties.

Enhanced nonvolatile resistive switching in dilutely cobalt doped TiO2 - Bogle, Kashinath A.; Bachhav, Mukesh N.; Deo, Meenal S.; Valanoor, Nagarajan; Ogale, Satishchandra B. (Applied Physics Letters, 2009)
Incorporation of dilute concentration of dopant having a valence state different than that of the host cation enables controlled incorporation proximity vacancy defects for local charge balance. Since nonvolatile resistive switching is a phenomenon tied to such defects, it can be expected to be influenced by dilute doping. In this work, we demonstrate that enhanced nonvolatile resistive switching is realized in dilutely cobalt doped TiO2 films grown at room temperature. We provide essential characterizations and analyses. We suggest that the oxygen vacancies in the proximity of immobile dopants provide well distributed anchors for the development of systematic filamentary tracks.
Keywords: cobalt; Doping; magnetic switching; random-access storage; titanium compounds; vacancies (crystal); valency

Nanoscale modulation of electronic states across unit cell steps on the surface of an epitaxial colossal magnetoresistance manganite film - Rana, Abhimanyu; Bogle, Kashinath A.; Game, Onkar S.; Patil, Shankar; Valanoor, Nagarajan; Ogale, Satishchandra B. (Applied Physics Letters, 2010)
The nature of electronic states near the edge of unit cell steps on the surface of epitaxial La(0.7)Sr(0.3)MnO(3) (LSMO) thin films grown by real-time reflection high energy electron diffraction monitored pulsed laser deposition is examined by scanning tunneling microscopy and scanning tunneling spectroscopy techniques. It is observed that the electronic states are strongly modulated near the step edge with considerably high gap at the edge and low gap on the terrace. This modulation weakens at low temperature. The temperature evolution of the density of states and the nature of gap in deep metallic state of LSMO are also discussed. (C) 2010 American Institute of Physics. [doi:10.1063/1.3455886]
Keywords: colossal magnetoresistance; electronic density of states; lanthanum compounds; magnetic epitaxial layers; Nanostructured materials; pulsed laser deposition; reflection high energy electron diffraction; scanning tunnelling microscopy; scanning tunnelling spectroscopy; strontium compounds

Ferroelectric and electrical characterization of multiferroic BiFeO3 at the single nanoparticle level - Vasudevan, R. K.; Bogle, Kashinath A.; Kumar, A.; Jesse, S.; Magaraggia, R.; Stamps, R.; Ogale, Satishchandra B.; Potdar, H. S.; Nagarajan, V. (Applied Physics Letters, 2011)
Ferroelectric BiFeO3 (BFO) nanoparticles deposited on epitaxial substrates of SrRuO3 (SRO) and La1-xSrxMnO3 (LSMO) were studied using band excitation piezoresponse spectroscopy (BEPS), piezoresponse force microscopy (PFM), and ferromagnetic resonance (FMR). BEPS confirms that the nanoparticles are ferroelectric in nature. Switching behavior of nanoparticle clusters were studied and showed evidence for inhomogeneous switching. The dimensionality of domains within nanoparticles was found to be fractal in nature, with a dimensionality constant of similar to 1.4, on par with ferroelectric BFO thin-films under 100 nm in thickness. Ferromagnetic resonance studies indicate BFO nanoparticles only weakly affect the magnetic response of LSMO. (C) 2011 American Institute of Physics. [doi: 10.1063/1.3671392]

Epitaxial magnetic oxide nanocrystals via phase decomposition of bismuth perovskite precursors - Bogle, Kashinath A.; Cheung, Jeffrey; Chen, Yong-Lun; Liao, Sheng-Chieh; Lai, Chih-Hung; Chu, Ying-Hao; Gregg, John M.; Ogale, Satishchandra B.; Valanoor, Nagarajan (Advanced Functional Materials, 2012)
The phase instability of bismuth perovskite (BiMO3), where M is a ferromagnetic cation, is exploited to create self-assembled magnetic oxide nanocrystal arrays on oxide supports. Conditions during pulsed laser deposition are tuned so as to induce complete breakdown of the perovskite precursor into bismuth oxide (Bi2O3) and metal oxide (M-Ox) pockets. Subsequent cooling in vacuum volatizes the Bi2O3 leaving behind an array of monodisperse nanocrystals. In situ reflective high energy electron diffraction beam is exploited to monitor the synthesis in real-time. Analysis of the patterns confirms the phase separation and volatization process. Successful synthesis of M-Ox, where M = Mn, Fe, Co, and Cr, is shown using this template-free facile approach. Detailed magnetic characterization of nanocrystals is carried out to reveal the functionalities such as magnetic anisotropy as well as larger than bulk moments, as expected in these oxide nanostructures.
Keywords: Bi2O3 evaporation; bismuth perovskites; epitaxial nanostructures; magnetic oxides; phase separation

TiO2-Au plasmonic nanocomposite for enhanced dye-sensitized solar cell (DSSC) performance - Muduli, Subas; Game, Onkar S.; Dhas, Vivek V.; Vijayamohanan, K.; Bogle, Kashinath A.; Valanoor, N.; Ogale, Satishchandra B. (Solar Energy, 2012)
Anatase TiO2 nanoparticles dressed with gold nanoparticles were synthesized by hydrothermal process by using mixed precursor and controlled conditions. Diffused Reflectance Spectra (DRS) reveal that in addition to the expected TiO2 interband absorption below 360 nm gold surface plasmon feature occurs near 564 nm. It is shown that the dye sensitized solar cells made using TiO2-Au plasmonic nanocomposite yield superior performance with conversion efficiency (CE) of similar to 6% (no light harvesting), current density (J(SC)) of similar to 13.2 mA/cm(2), open circuit voltage (V-oc) of similar to 0.74 V and fill factor (FF) 0.61; considerably better than that with only TiO2 nanoparticles (CE similar to 5%, J(SC) similar to 12.6 mA/cm(2), V-oc similar to 0.70 V, FF similar to 0.56). (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Anatase TiO2; Au; Dye-sensitized solar cells; Hybrid composite; hydrothermal

Scaling behavior of resistive switching in epitaxial bismuth ferrite heterostructures - Rana, Abhimanyu; Lu, Haidong; Bogle, Kashinath A.; Zhang, Qi; Vasudevan, Rama; Thakare, Vishal; Gruverman, Alexei; Ogale, Satishchandra; Valanoor, Nagarajan (Advanced Functional Materials, 2014)
Resistive switching (RS) of (001) epitaxial multiferroic BiFeO3/La0.67Sr0.33MnO3/SrTiO3 heterostructures is investigated for varying lengths scales in both the thickness and lateral directions. Macroscale current-voltage analyses in conjunction with local conduction atomic force microscopy (CAFM) reveal that whilst both the local and global resistive states are strongly driven by polarization direction, the type of conduction mechanism is different for each distinct thickness regime. Electrode-area dependent studies confirm the RS is dominated by an interface mechanism and not by filamentary formation. Furthermore, CAFM maps allow deconvolution of the roles played by domains and domain walls during the RS process. It is shown that the net polarization direction, and not domain walls, controls the conduction process. An interface mechanism based on barrier height and width alteration due to polarization reversal is proposed, and the role of electronic reconstruction at the interface is further investigated.